Implementasi Metode Cerita dalam Menanamkan Akhlak Mulia Peserta Didik Kelas V di Madrasah Ibtidaiyah - Muhamad Isrok Sa'id; Middya Boty; Ines Tasya Jadidah (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This research discusses the implementation of the story method in instilling noble morals in fifth grade students of MI Hijriyah II Palembang. This research is motivated by the importance of the story method applied in learning to instill noble morals in students. The story method is used by MI Hijriyah II SKI teachers in teaching to make it easier for students to understand the material and provide examples through the stories discussed. This study aims to describe the form of instilling noble morals in students, describe the implementation of the story method in instilling morals in grade V students, and factors that influence the implementation of the story method. This research is a descriptive qualitative research. Data collection was done through observation, interviews, and documentation. The validity of this research data is guaranteed by triangulation techniques, namely triangulation of sources, techniques, and theories. The results of this study indicate that: 1) The story method is implemented through three stages, namely: Preparation includes determining learning objectives, preparing learning tools, and learning resources. Implementation includes conveying learning objectives, conditioning students, and delivering stories orally. Closing includes summarizing the content of the story and giving assignments. 2) Factors that influence are inhibiting factors including students easily bored, lack of focus and enthusiasm, lack of infrastructure and time available. Supporting factors include the story method is easier to instill noble morals in students, stories affect students' feelings, and easier class control.